Relations Between Parental Communication Pattern and Parents’ Education With Social Science Learning Outcomes - Prawanti, Lia Titi; Sukardi, Sukardi (Universitas Negeri Semarang, 2019)
The background of this study is the findings from the Research and Development Center of Curriculum, Department of Education in 2007 stated that there are various problems in Social Science Studies. The problem in SD Gugus Sunan Giri, Demak Subdistrict is the result of Social Science learning in grade IV are relatively low. The purpose of this research is to know whether there is a relationship between communication pattern with social science learning outcomes at 4th graders in elementary school Gugus Sunan Giri Kecamatan Demak Kabupaten Demak. This research was a correlational research with quantitative approach. The amount of sample is 100 students from the whole population with the quota sampling. The technique of data collection are observation, interview, questionnaires, test, and documentation. The analysis data using descriptive model and hypothesis experiment. The result of this research show that: (1) communication pattern is suffient; (2) background of parents education is deficient; (3) the result of social science learning is moderate; (4) there is a positive and significant correlation between communication pattern with the result of social science learning, shown by rcount 0,572; (5) there is a positive and significant correlation between background of parents education with the result of social science learning, shown by rcount 0,370; (6) there is a positive and significant correlation between communicatin pattern and background of parents education with the result of social science learning, shown by rcount 0,579; (7) the contribution of communication pattern with the result of social science learning is 32,7%; (8) the contribution of parent’s education background with theresult of social science learning is 13,7%; (9) the contribution of communication pattern and background of parents eduation with the result of social science learning is 33,5%.